Early results of high tibial osteotomy versus combined arthroscopic surgery - Zhang, Zhenbin; Yan, Zhaolong; Wang, Gongteng; Zhang, Wenqi; Li, Guangxing; Wang, Xufeng; Sun, Huaqiang; Li, Shufeng (Frontiers in Surgery, 2024)
Objective To investigate the early effect of high tibial osteotomy (HTO) compared with combined arthroscopic surgery. Methods A retrospective study was conducted on patients who underwent HTO at The First Affiliated Hospital of Shandong First Medical University from January 2018 to January 2022. 138 patients (163 knees) with knee osteoarthritis (KOA) treated with HTO were selected. The medial proximal tibial angle (MPTA), joint line convergence angle (JLCA), femoral tibial angle (FTA), hip-knee-ankle (HKA) angle, weight-bearing line (WBL) ratio of the knee joint, opening gap, opening angle, American Knee Society score (KSS), US Hospital for Special Surgery (HSS) score, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score were measured to determine the different effects between HTO and HTO combined with arthroscopic by logistic regression analysis. Results Patients with HTO combined with arthroscopic surgery have improved functional scores as well as imaging perspectives compared to preoperative. By multivariate logistic analysis, it was concluded that arthroscopic surgery and gender are influential factors in the outcome of HTO surgery. The postoperative KSS score was 2.702 times more likely to be classified as excellent in the HTO combined with arthroscopy group than in the HTO group [Exp (β) = 2.702, 95% CI (1.049–6.961), P = 0.039]; the postoperative KSS score was 0.349 times more likely to be classified as excellent in women than in men [Exp (β) = 0.349, 95% CI (0.138–0.883), P = 0.026]. Conclusion Better results with HTO combined with arthroscopic surgery. HTO combined with arthroscopy is a better choice in the surgical treatment of KOA.